Geo-spatial analysis of high-risk fertility behaviors and child stunting in Ethiopia - Zewdia, Wondaya Fenta; Asmelash, Daniel; Asmelash, Yemane (Frontiers in Public Health, 2024)
BackgroundThe process of childbirth involves significant risks, particularly when certain high-risk fertility behaviors (HRFBs) are observed. HRFB of birth includes maternal age below 18 years or above 34 years at the time of childbirth, having a child born after a short birth interval (24 months), and having a high parity (more than three children). The majority of child stunting cases were linked to high-risk reproductive practices. Stunted children are those whose height-for-age Z-score is less than –2SD (standard deviation) from the median of a reference population. This study aimed to investigate the spatial association between HRFB of birth and stunting in under-five children across Ethiopia’s administrative zones.MethodThis study used cross-sectional data from the latest Mini Ethiopian Demographic and Health 2019 Survey, which included a weighted sample of 4,969 under-five children from 64 administrative zones. Spatial model analysis, specifically the spatial Durbin model, was used to examine the association between HRFB of birth and stunting in children. ArcGIS 10.8 was used for mapping and SAS 9.4 was used for model analysis.ResultsThe average mean proportion of HRFB of birth to the rate of stunting in children at the zonal level in Ethiopia was observed to be 58 and 36%, respectively, across Ethiopian zones. Children whose mothers displayed HRFB of birth and who were stunted were 24% at all times. The median value of HRFB of birth and stunting were 0.61 and 0.36, respectively. The average vegetable index and the livestock index across Ethiopian zones showed spatial variations of 0.57 and 0.12, respectively. In the selected spatial Durbin model, the deviance value was very small, indicating that the model fit the data well.ConclusionThe study found a high prevalence and significant spatial variation in both HRFB of birth and stunting across the Ethiopian zones. The spatial distribution of both HRFB of birth and stunting were found to be significantly clustered in the administrative zones of Ethiopia. These results emphasize the need for targeted interventions to address HRFB and stunting, supporting Ethiopia in achieving its Sustainable Development Goals.